Mycophenolate mofetil in multiple sclerosis: a multicentre retrospective study on 344 patients. Issue 3 (23rd May 2013) - Michel, L; Vukusic, S; De Seze, J; Ducray, F; Ongagna, J C; Lefrère, F; Jacq-Foucher, M; Confavreux, C; Wiertlewski, S; Laplaud, D A
Abstract : Objectives: Mycophenolate mofetil (MMF) is an immunosuppressive agent, sometimes used as a disease-modifying therapy for multiple sclerosis (MS). Several studies have reported the relative safety of this treatment but, to date, its efficacy has rarely been described. We performed a retrospective study to assess the safety and efficacy of MMF in patients with MS. Methodology: Three French MS centres included all of their patients treated by MMF. The main outcome criterion was annualised relapse rate (ARR) in the 1 year period after onset of MMF compared with the 1 year control period. Treatment with another immunosuppressive drug, such as mitoxantrone or cyclophosphamide, in the 2 years preceding initiation of MMF was included in a subgroup analysis. MMF safety and progression of the Expanded Disability Status Scale (EDSS) score were also assessed. Results: 344 patients were included; 149 patients were previously treated with another immunosuppressant (IS group). Mean MMF treatment duration was 25.3±1.1 months. During the 1 year control period, ARR was 1.11±0.08, and for the 1 year treatment period, ARR was reduced significantly to 0.35±0.05 (p<0.0001, Wilcoxon paired test). Adverse events (occurring in 11% of patients) were mainly digestive disorders, benign infections, asthenia and transitory lymphopenia. Concerning the progression of disability, in the subgroup of patients without previous immunosuppressant treatment, EDSS remained stable between initiation and 1 year after the beginning of MMF. Interpretation: Our results suggest that MMF can improve or stabilise MS patients and can be used as an alternative therapy.